NETFLIX, THE SUCCESS OF A GLOBAL STORYTELLING - Goncharenko, Mikhail; Wang, Zhen Zhen; Yang, Xu Yi; Najma, Ahmed Ismail; Dong, Rui Xu (INTI International University, 2023)
The global expansion of Netflix represents a transformative journey in the entertainment industry. Initially launched as a DVD rental-by-mail service in the United States in 1997, Netflix gradually evolved into a streaming giant that transcended borders. The company's strategic pivot to online streaming in 2007 laid the foundation for its international expansion. Netflix's global rollout began in 2010, and since then, it has aggressively entered diverse markets worldwide, overcoming challenges related to content localization, cultural differences, and regulatory frameworks. The platform's global success can be attributed to its commitment to producing original content tailored for diverse audiences, fostering a binge-watching culture, and leveraging advanced data analytics to personalize recommendations. The impact of Netflix's global presence extends beyond entertainment consumption, influencing viewing habits, content creation dynamics, and the competitive landscape of the media industry. The story of Netflix going global exemplifies the power of digital innovation, content strategy, and adaptability, showcasing how a company can transcend geographical boundaries to become a ubiquitous force in the ever-evolving global entertainment landscape.